OBESITAS DAN TINGKAT STRESS MENYEBABKAN KEJADIAN PREEKLAMSIA PADA IBU HAMIL - Siti Husaidah; Yulia Devi Putri; Rini Harlina (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
In Indonesia, one of the leading causes of maternal mortality is preeclampsia which ranks second with a percentage of 1,066 cases (25%). Preeclampsia occurs due to various factors, namely age, education level, family support, weight gain (obesity). This study aims to determine the relationship between obesity and stress levels with the incidence of preeclampsia in pregnant women at Health Center Botania Dan Sei. Lekop Batam City in 2021. The design of this study used observational analytic with a cross sectional design. The respondents in this study were 38 pregnant women. The sampling technique used was purposive sampling. The results of the chi square statistical test showed p value = 0.000 ( 0.05) so that Ho was rejected, this indicates a relationship between obesity and stress levels with the incidence of preeclampsia in pregnant women at Health Center Botania Dan Sei. Lekop Batam City in 2021. The conclusion of this study is obesity and stress levels can cause preeclampsia. It is recommended for pregnant women to apply a healthy lifestyle such as exercise, healthy eating habits, as well as doing distraction and relaxation to prevent the occurrence of preeclampsia in pregnant women.